Study Analysis of Brisk Walking Exercise Effects on Cardio-Respiratory Fitness Among Middle Age Adult People: Literature Review - Marianna R. G. Tompunu; Ballsy C. A. Pangkey (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Non-Communicable Disease (NCD) are diseases that cannot be transmitted from one individual to another. In other words, the disease does not harm other people. The community belongs to one main NCD group with the same risk factor (common underlying risk factor). Non-communicable diseases can be prevented by avoiding risk factors and achieving a good level of fitness. One way to improve fitness is by doing brisk walking. Objectives: The purpose of this study was to determine the effect of brisk walking on cardio-respiratory fitness in the middle adult age group. Methods: In the strategy to find the journal framework used is PICOT. The data sources used were taken from the e-resources database of the National Library of Indonesia, Pubmed, and Google Scholar, then selected using the PRISMA flow diagram to produce nine articles. Each article has been described and criticized in the form of a matrix table using a simplified approach method. Results: The results of the study found that brisk walking had a significant effect on cardio-respiratory fitness in the middle adult age group. Conclusion: This exercise can also be recommended for anyone who wants to live a healthy life and is recommended to be done at home with the implementation according to the recommendations. The ineffectiveness of brisk walking can also be influenced by several factors so before doing this exercise, the indications and contraindications should be considered.